Performance Analysis of Volume Loads of (Services and Transmission) Traffic in VPN Networks: A Comparative Study - Mohammed, Subhi Aswad (Al-Nahrain Journal for Engineering Sciences, 2019)
This paper proposes a design for a network connected over public networks using Virtual Private Network (VPN) technique. The network consists of five sites; center server and four customer service sites, each site consists of a number of LANs depending on the user services requirements. This work aims to measure the effect of VPN on the performance of a network. Four approaches are implements: Network design without using VPN, network design using VPN with centralized servers, network design using VPN with distributed servers, and network design using server load balance.The OPNET and BOSON   simulation results show higher response time for packet transmission due to effect of VPN tunneling. The concurrent activation of application execution is used as a solution to the delay problem of the initial timing period while the application proceeds. The results dealing with QoS are E-mail, FTP, voice services traffic and IP traffic dropped. The VPN Tunnels is in the range of (0.01 to 0.02) sec.; along with this simulator there are four VPN tunnels in the network. Also, a special server’s load balance is used to manage distribution of the server processing load across all other network servers to achieve the best response